Model of Information Disclosure in a Multilevel Social-Economic System with Information Asymmetry by the Example of a Regional Market of Property Rights - Alim Gurtuev, Muslim Chazhaev, Rustam Yalmaev, Zaur Ivanov, Aminat Dumanova, Macca Yalmaeva (International Journal of Advanced Science and Technology, 2020)
The behavior of economic agents in an innovative process may be reduced to the problem of decision making under uncertainty in Knight’s sense. The primary problem is that of cognitive limitations, characteristic for actual economic agents. It allows opportunism, i.e. inclination of individuals to deceive or to distort information for their own advantage, doing that in an indirect way. Bounded cognitive abilities and opportunism, taken together, result in the problem of knowledge asymmetry – namely, even if the information about essential aspects of a deal is available to all its participants, one of the parties lacks competences necessary to process that information.Knowledge asymmetry in the system of innovative investment results in distortions of resources allocation efficiency and market failures related to the effects of disadvantageous selection and post-contract opportunism. An important factor determining the parameters (and the very existence) of market equilibrium in such a system is the character of distortions in the economic agents’ preferences. These can be divided into two classes – individual deviation from risk-neutrality and deviations of the subjective probability assessment of distribution when forecasting future events from the true distribution. This division is important for studying the systems with uncertainty. The first class of distortions is observed both in systems with risk and in systems with uncertainty; it is usually considered to be an immanent characteristic of an agent, does not change with time and is described with the Arrow-Pratt measure in models. Its influence on equilibrium is well studied. The second class is observed only in systems with uncertainty and changes with time for each agent. Its influence on equilibrium under various mechanisms of market organization is rather poorly studied.The paper presents the model of property rights market with an infrastructural institution disclosing non-personalized information under the situation when a regional economic system is a combination of market elements, administrative and shadow economy. In such a system agents make decisions under uncertainty, as for each object of property there is hidden, non-transferrable information essential for assessment. Under such conditions, the influence of subjective assessment deviations on the market equilibrium can be described as Bayesian probability model of adverse selection.In the elaborated model, the equilibrium parameters are theoretically analyzed. Expressions for assessing ask and bid prices are obtained. It is shown that information asymmetry in the property rights market, with the account of the specific features of economic systems of the Russian regions, leads to irrational allocation of investment resources.It is shown that the infrastructural institutions disclosing non-personalized information are not only unable to efficiently counteract adverse selection, but facilitate it.